Stroke in HIV-infected individuals with and without HCV coinfection in Spain in the combination antiretroviral therapy era - Alvaro-Meca, Alejandro (PLoS One, 2017)
The incidence of stroke in human immunodeficiency virus (HIV)–infected individuals has been well analyzed in recent epidemiological studies. However, little is known about the specific contribution of hepatitis C virus (HCV) infection to stroke among HIV-infected individuals. The aims of this study were to analyze trends in the incidence rates of stroke in HIV-infected individuals during the combination antiretroviral (cART) era in Spain and to categorize them by the presence or absence of HCV coinfection. We analyzed hospital discharges with a diagnosis of stroke in Spain according to ICD-9-CM during 1997–2013. The study period was divided into four calendar periods (1997–1999, 2000–2003, 2004–2007, and 2008–2013). Patients were classified according to HCV serology. The number of HIV-infected patients was estimated based on data from the National Centre of Epidemiology. We calculated incidence rates (events per 10,000 patient-years) and in-hospital case fatality rates (CFR). The incidence of hemorrhagic stroke (HS) decreased in HIV-monoinfected patients (15.8 [1997–1999] to 6.5 [2008–2013]; P<0.001) and increased in HIV/HCV-coinfected patients (1.3 [1997–1999] to 5.5 [2008–2013]; P<0.001). The incidence of ischemic stroke (IS) decreased in HIV-monoinfected patients (27.4 [1997–1999] to 21.7 [2008–2013]; P = 0.005) and increased in HIV/HCV-coinfected patients (1.8 [1997–1999] to 11.9 [2008–2013]; P<0.001). The CFR was 3.3 times higher for HS than for IS for the whole study period. The CFR of HS in HIV-monoinfected patients decreased significantly (47.4% [1997–1999] to 30.6% [2008–2013]; P = 0.010) but did not change significantly among HIV/HCV-coinfected patients (41.4% [1997–1999] to 44.7% [2008–2013]; P = 0.784). The CFR of IS in the whole HIV-infected population decreased significantly (14.6% [1997–1999] to 10.9% [2008–2013]; P = 0.034), although no significant differences were found when each group was analyzed separately. In conclusion, after the introduction of cART, HS and IS rates decreased in HIV-monoinfected individuals, but increased steadily in HIV/HCV-coinfected individuals.